Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/ismej.2017.182
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of hydrogen peroxide at the ocean’s surface: the influence of the microbial community on the realized thermal niche of Prochlorococcus

Abstract: Prochlorococcus, the smallest and most abundant phytoplankter in the ocean, is highly sensitive to hydrogen peroxide (HOOH), and co-occurring heterotrophs such as Alteromonas facilitate the growth of Prochlorococcus by scavenging HOOH. Temperature is also a major influence on Prochlorococcus abundance and distribution in the ocean, and studies in other photosynthetic organisms have shown that HOOH and temperature extremes can act together as synergistic stressors. To address potential synergistic effects of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 85 publications
1
54
1
2
Order By: Relevance
“…EZ55 -effectively dropped the HOOH to zero and facilitated the growth of all cultured ecotypes of Prochlorococcus. Consistently, we and others have found that treatment of the media with a chemical scavenger of HOOH, pyruvate, also promotes Prochlorococcus growth (Berube et al, 2015;Ma et al, 2017) [notably, additions of catalase to the medium do not support growth of Prochlorococcus; we have found that commercially available (e.g., bovine) catalase is unstable in seawater and becomes a net producer rather than consumer of ROS].…”
Section: Prochlorococcus Is Helped Via Hooh Removalsupporting
confidence: 85%
See 3 more Smart Citations
“…EZ55 -effectively dropped the HOOH to zero and facilitated the growth of all cultured ecotypes of Prochlorococcus. Consistently, we and others have found that treatment of the media with a chemical scavenger of HOOH, pyruvate, also promotes Prochlorococcus growth (Berube et al, 2015;Ma et al, 2017) [notably, additions of catalase to the medium do not support growth of Prochlorococcus; we have found that commercially available (e.g., bovine) catalase is unstable in seawater and becomes a net producer rather than consumer of ROS].…”
Section: Prochlorococcus Is Helped Via Hooh Removalsupporting
confidence: 85%
“…As described earlier, in our initial study identified 33 catalase-positive heterotrophic strains that could help Prochlorococcus grow on plates (Morris et al, 2008). Importantly, for many of the eukaryotes and for Prochlorococcus, the HOOH decay rates were not significant unless the cells were at much higher concentrations than they exist in the ocean (Petasne and Zika, 1997;Morris et al, 2011;Ma et al, 2017), and thus may not serve as significant sinks in situ. Other microbes shown to degrade HOOH in monoculture could potentially also serve as helpers.…”
Section: Who Removes Hooh In the Ocean?mentioning
confidence: 68%
See 2 more Smart Citations
“…This 77 variability may impose divergent selection on symbiont thermal traits, with potential feedbacks 78 on the thermal tolerance of the hosts themselves. 79 We used common garden experiments (in vitro) to characterize symbiont thermal niches 80 with a culture collection of Snodgrassella and Gilliamella, two bacterial species that are 81 ubiquitous across honeybees and bumblebees [17]. Symbionts of these two bee lineages belong under 5% CO2, from 12-48 °C in increments of 4 °C.…”
Section: Introductionmentioning
confidence: 99%